The Effect of Leverage and Profitability on Tax Avoidance with Company Transparency as a Moderating Variable - Nuur Ainii Safiinatunnajah; Hari Setiyawati (Budapest International Research and Critics University, 2022)
The causes of the high incidence of tax evasion in Indonesia must be identified. This study intends to examine and assess the influence of ownership structure and company transparency on tax evasion, with profitability serving as a moderating variable, among industrial businesses listed on the Indonesia Stock Exchange between 2018 and 2020. This study was created with quantitative methodologies in mind. This study obtained information from www.idx.co.id and the financial accounts of the firm. To get up to sixty-five firms, a purposeful sample was employed. 195 samples were collected over three years of monitoring. The hypotheses were then assessed using multiple linear regression analysis and statistical test analysis on the acquired sample data. Results indicated that DER and ROA had a significant positive impact on tax evasion. Corporate Transparency Reduces the Effects of DER and Return on Assets on Tax Avoidance.